Mutual Coupling Reduction of E-Shaped MIMO Antenna with Matrix of C-Shaped Resonators - Raghad Ghalib Saadallah Alsultan; Gölge Ögücü Yetkin (International Journal of Antennas and Propagation)
E-shaped multiple-input-multiple-output (MIMO) microstrip antenna systems operating in WLAN and WiMAX bands (between 5 and 7.5 GHz) are proposed with enhanced isolation features. The systems are comprised of two antennas that are placed parallel and orthogonal to each other, respectively. According to the simulation results, the operating frequency of the MIMO antenna system is 6.3 GHz, and mutual coupling is below −18 dB in a parallel arrangement, whereas they are 6.4 GHz and −25 dB, respectively, in the orthogonal arrangement. The 2 × 3 matrix of C-shaped resonator (CSR) is proposed and placed between the antenna elements over the substrate, to reduce the mutual coupling and enhance the isolation between the antennas. More than 30 dB isolation between the array elements is achieved at the resonant frequency for both of the configurations. The essential parameters of the MIMO array such as mutual coupling, surface current distribution, envelop correlation coefficient (ECC), diversity gain (DG), and the total efficiency have been simulated to verify the reliability and the validity of the MIMO system in both parallel and orthogonal configurations. The experimental results are also provided and compared for the mutual coupling with simulated results. An adequate match between the measured and simulated results is achieved.